Schools as the Foundation of Corruption Prevention: From Knowledge to Action - Nurcahyani, Dwi; Bakri, Bakri; Najih, Aizun; Maftuhatin, Lilik; Zaki, Muhamad; Nidhom, Misbahun; Susilowati, Henny (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This study investigates how schools can serve as strategic platforms for corruption prevention by synthesizing findings from a wide range of literature, including academic journals, policy documents, and anti-corruption education programs in Indonesia. The research addresses the growing concern that anti-corruption efforts remain abstract in educational settings, with a gap between knowledge and actionable behavior. Concrete actions identified in this study include student-led integrity projects, transparent class budgeting practices, and school-wide campaigns promoting ethical behavior. These practices illustrate how anti-corruption values—such as honesty, responsibility, and fairness—can be internalized through daily school routines and decision-making processes. The implementation strategies discussed are drawn from both documented best practices and theoretical frameworks. Notable sources include educational programs initiated by the Corruption Eradication Commission (KPK) and pilot schools implementing the Kurikulum Merdeka and Profil Pelajar Pancasila. These strategies include experiential learning, integration of anti-corruption themes into project-based curricula, digital platforms for school governance transparency, and teacher professional development focused on ethics education. Recommendations emphasize the need for a coordinated approach involving the Ministry of Education, school leaders, teachers, parents, and anti-corruption bodies like the KPK. Concrete suggestions include embedding anti-corruption modules in teacher training programs, establishing school-community integrity pacts, and forming regional networks to share successful initiatives. This synergy between policy, pedagogy, and local stakeholder engagement is essential to cultivate a generation committed to integrity and transparency.